2008
DOI: 10.1016/j.apcatb.2007.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic discoloration of Methyl Orange on innovative parylene–TiO2 flexible thin films under simulated sunlight

Abstract: Parylene films loaded with TiO 2 are reported as photocatalysts in azo dye discoloration processes. The TiO 2 loading of the parylene film was 0.32% (w/w) and the amount of TiO 2 on the film was about two orders of magnitude below the TiO 2 added in suspension to discolore the same solution of Methyl Orange used as a probe. The parylene/TiO 2 films showed a similar activity in the presence of O 2 or H 2 O 2 during the discoloration of dyes. This shows the efficient role of O 2 as e cb À scavenger. The photonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…Actually, addition of H 2 O 2 enhanced the reaction. Zhiyong et al [47] also reported that addition of H 2 O 2 (1 mM) to methyl orange solution mediated TiO 2 Degussa P25 (0.5 g/l) under sunlight irradiated photocatalyst brought about methyl orange degradation in 1 h.…”
Section: Oxidizing Agents Effect On Photocatalytic Degradation Of Dyementioning
confidence: 94%
See 1 more Smart Citation
“…Actually, addition of H 2 O 2 enhanced the reaction. Zhiyong et al [47] also reported that addition of H 2 O 2 (1 mM) to methyl orange solution mediated TiO 2 Degussa P25 (0.5 g/l) under sunlight irradiated photocatalyst brought about methyl orange degradation in 1 h.…”
Section: Oxidizing Agents Effect On Photocatalytic Degradation Of Dyementioning
confidence: 94%
“…The following investigations are the proofs of enhancement of the efficiency of TiO 2 by doping [23,[38][39][40][41][42][43][44][45][46][47]. Krishna et al [48] also reported a 2.6 times higher rate coefficient for PHF-TiO 2 over TiO 2 for the degradation of triazine monoazo compound Pricion red MX-5B.…”
Section: Titanium Dioxide Photocatalystmentioning
confidence: 98%
“…The zirconia-modified Parylene film demonstrated the enhanced fracture resistance of dental ceramics [9]. The flexible polymer titania Parylene obtained by the immersion of a Parylene thin film (45 μm) into an alcohol suspension of TiO 2 Degussa P25 and heated at 180°C, demonstrated high photocatalytic activity in the discoloration of azo-dyes [10,11]. In another study, the authors described the liquid phase deposition of titania onto Parylene-coated Si wafers as a prerequisite for their evaluation as materials for bio-implant applications [12].…”
Section: Introductionmentioning
confidence: 98%
“…Working with real wastewater samples, which are polluted by different types of organic substances lead to determine the true effectiveness of the photocatalytic treatment. Methyl orange and Methylene blue has extensively studied in order to know their photodegradation mechanism, which takes place mainly by unstable intermediates cations formation and successive oxidation reactions [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As TiO 2 is the most recognized and employed material in photocatalysis, many efforts have been devoted to improve its effectiveness; thus, noble metal addition [11,18], non-metals doping [19,20], sulfation and fluorination [4,[21][22][23][24][25][26][27][28][29][30] among others have been reported to be suitable alternatives for titania modification. Taking into account that the practical application of TiO 2 is not in the form of dispersions, many studies in this area have been also focused on supported TiO 2 being photolyzed in the presence of a pollutant during a continuous cleaning process [14,16,28,31,32], in these processes the separation of the pollutant from the processed solution at the end of the process it is not necessary.…”
Section: Introductionmentioning
confidence: 99%